From current algebra to quantum chromodynamics : - Cao, Tian Yu (Cambridge University Press, 2010)
"The advent of quantum chromodynamics (QCD) in the early 1970s was one of the most important events in twentieth-century science. This book examines the conceptual steps that were crucial to the rise of QCD, placing them in historical context against the background of debates that were ongoing between the bootstrap approach and composite modeling, and between mathematical and realistic conceptions of quarks. It explains the origins of QCD in current algebra and its development through high-energy experiments, model-building, mathematical analysis and conceptual synthesis. Addressing a range of complex physical, philosophical and historiographical issues in detail, this book will interest graduate students and researchers in physics and in the history and philosophy of science"--